taking (x-1)^2 common
[(x-1)^2](x-1-1)=0
(x-1)^2)(x-2)=0
so x=1,1 or 2
2007-01-02 11:16:30
·
answer #1
·
answered by raj 7
·
0⤊
0⤋
Everyone else is doing it the right, mathematical way.
I'd like to point out one other way, though.
Call z = x - 1, for a moment. Then you have:
z³ - z² = 0
z³ = z²
There are only two numbers where you get the same thing when you square them as when you cube them, 1³ = 1² = 1 and 0³ = 0² = 0.
So if z = 1, then 1 = x - 1, so x = 2.
And if z = 0, then 0 = x - 1, so x = 1.
Just another way of looking at it.
2007-01-02 11:21:06
·
answer #2
·
answered by Jim Burnell 6
·
0⤊
0⤋
First notice that both terms have at least 2 factors of (x-1) in common. This means that we can take them out as follows:
(x-1)^3 - (x-1)^2 = [(x-1)^2][(x-1) - 1]
Simplifying the RHS and setting it equal to 0, we get:
[(x-1)^2][x-2] = 0
So we have that x = 1 OR x = 2
2007-01-02 11:17:12
·
answer #3
·
answered by alsh 3
·
0⤊
0⤋
First factor out an (x - 1) term:
(x - 1)[ (x - 1)² - (x - 1) ] = 0
And then again:
(x - 1)(x - 1) [ (x - 1) - 1 ] = 0
Now simplify the stuff in the brackets:
(x - 1)(x - 1)(x - 2) = 0
So the answers are x = 1 or x = 2
2007-01-02 11:16:23
·
answer #4
·
answered by Puzzling 7
·
0⤊
0⤋
Since when you subtract they equal 0, you could always make them equal to each other.
(x-1)^3 = (x-1)^2
(x-1)(x-1)(x-1) = (x-1)(x-1)
x^3 + 1 = x^2 - 2x +1
x^3 = x^2 -2x
Factor out an x:
x^2(x^2 = x - 2)
x^2 = x - 2
x = (x-2)^1/2
2007-01-02 11:24:11
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
ok first u foil everything out
solve for the latter part of the equation primarily.
u get x^2-2x+1. then u multiply one (x-1) term to that and you get
x^3-3x^2+x-1subtract the two equations and solve for x
2007-01-02 11:17:45
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
(x-1)^3 - (x-1)^2 =0
(x-1)^2[x-1-1] = 0
(x-1)^2(x-2)= 0
x-2 = 0
x=2
(x-1)^2=0
x-1=0
x=1
x=1 is a double root
2007-01-02 11:20:20
·
answer #7
·
answered by ironduke8159 7
·
0⤊
0⤋
(x-1)^3 = (x-1)^2
[(x-1)^3] / [(x-1)^2] = [(x-1)^2] / [(x-1)^2]
(x-1) = 1
x= 1+1
x=2
2007-01-02 11:17:49
·
answer #8
·
answered by arturo r 2
·
0⤊
0⤋
1st (x-1)(x-1)(x-1)-(x-1)(x-1)=0
2nd you do foil... x-1(x-1)=x^2- 2x+1
3rd u rewrite it... (X-1)(x^2-2x+1)-(X^2-2x+1)=0
4th
2007-01-02 11:30:43
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
i dont feel like typing it all out
2007-01-02 11:16:12
·
answer #10
·
answered by puff 3
·
0⤊
2⤋